Assessment of Quality of Life in Patients with Cushing's Syndrome (Journal of Pharmaceutical Negative Results, 2022)
In this article, the author analyzes the quality of life of patients with Cushing's syndrome depending on the duration of hypercortisolemia and disease activity. They prospectively examined 48 patients with Cushing's syndrome living in different regions of the Republic of Uzbekistan. Features and the course of Cushing's syndrome on the patient's quality of life led to the development of a special questionnaire for patients with Cushing's syndrome, which reflects the aspects that cause the greatest concern in patients.